PEMEROLEHAN BAHASA ANAK USIA 3 TAHUN PADA TATARAN FONOLOGI - Mardhyana, Zilvia (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is a communication device that humans use to interact with fellow humans. They are dynamic and unique because they will continue to grow and grow as the ages grow. Language development may be marked by either a new term or a change in its meaning. Every language has its own distinctive feature. The purpose of this study is to identify the language of 3-year-olds by analyzing spoken speech. The method used is a qualitative descriptive method with a competent libat. In this case the writer described the results of his analysis. Researchers listen closely and listen to speech uttered by children, as well as researchers engage directly in communication activities and interact with children on the subject of research. Researchers ran a diagnostic analysis into the phonology landscape, with the majority of 3-year-olds removing or replacing the phones as they should. It is a fair one, since at age 3 an articulation and mastery of a child's language are not yet adequate, so it is best to tell a story and communicate well, for that is how the child has gained a new language.